2019
DOI: 10.1108/ebr-04-2018-0075
|View full text |Cite
|
Sign up to set email alerts
|

Friends with benefits

Abstract: Purpose This two-country comparative study’s purpose is to investigate antecedents to, and the consequences of a sense of belonging to a firm’s Facebook community. Design/methodology/approach The model was grounded in the theory of sense of community and tested through structural equation modelling. Consumer panels were used via online surveys. Findings Of the three antecedents hypothesised to influence an individual’s sense of belonging, enjoyment is a very strong predictor in both countries; while the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 81 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…The study selected Facebook as the research context because Facebook is a social network platform that has overwhelming popularity and offers abundant and diverse examples of SMBCs [47,48]. In line with other literature [49,50], the target was not only a single SMBC, but rather a more general approach of members of brand-initiated SMBCs (i.e., not consumer-initiated) in which the participants were instructed to refer to the SMBC to which they belonged.…”
Section: Methodsmentioning
confidence: 99%
“…The study selected Facebook as the research context because Facebook is a social network platform that has overwhelming popularity and offers abundant and diverse examples of SMBCs [47,48]. In line with other literature [49,50], the target was not only a single SMBC, but rather a more general approach of members of brand-initiated SMBCs (i.e., not consumer-initiated) in which the participants were instructed to refer to the SMBC to which they belonged.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed that the older the children were when they browsed accessible information, the better their counterfactual thinking skills and the number of round-trip choices therefore increased as they sought to minimize future regrets. Ortiz et al (2017) found that a sense of belonging has the greatest influence on an individual's participation in the provision of information, and three factors influence this sense of belonging: hedonism, dependence and trustworthiness of information (Wiese and Akareem, 2019). Younger children who develop counterfactual thinking skills more slowly tend to follow personalized recommendations and become dependent on accessible information, as they believe that personalized recommendations have the potential to reduce search costs and avoid cognitive overload.…”
Section: Impact Of Information Accessibilitymentioning
confidence: 99%
“…, 2019), it is surprising how the majority of studies have examined the SOB antecedents in the online consumer behavior context (e.g. Peng and Chen, 2020; Wiese and Akareem, 2019; Yang, 2019), especially by exploring its relationship with satisfaction (Chen et al. , 2020; Zhou et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the relevance of this construct in the tourist field (Hung et al, 2019), it is surprising how the majority of studies have examined the SOB antecedents in the online consumer behavior context (e.g. Peng and Chen, 2020;Wiese and Akareem, 2019;Yang, 2019), especially by exploring its relationship with satisfaction (Chen et al, 2020;Zhou et al, 2019;Lin et al, 2014). Indeed, even if both SOB and satisfaction have been conceptualized as two emotional constructs, SOB can be considered as an outcome since it leads to stronger individuals' reactions with respect to satisfaction (Zhou et al, 2019).…”
Section: Literature Review 21 Sense Of Belongingmentioning
confidence: 99%